Metacognitive cultural intelligence and service delivery at casual dining restaurants in Bloemfontein - Desere Kokt; Puseletso M. Sentso (SA Journal of Human Resource Management, 2024)
Orientation: Workplace diversity and intercultural interaction are undisputed realities in the new world of work. This is especially true for casual dining restaurants that are labour intensive and customer-oriented, catering for culturally diverse patrons.